Determinasi Faktor Psikososial terhadap Kesehatan Mental Mahasiswa Matematika Universitas Mataram Selama Penyusunan Skripsi - Sahadatin, Aulia; Anggara, Rosa; Baskara, Zulhan Widya; Putri, Dina Eka (Universitas Mataram, 2025)
This study examines the relationship between undergraduate thesis preparation and the mental health of Mathematics students at Universitas Mataram, focusing on key factors that influence the thesis process. These factors include motivation to graduate on time, peer support/social environment, availability of learning resources, and supervisor support. The findings indicate that motivation to graduate on time (x1) has the strongest positive impact on mental health. Additionally, supervisor support (x4) and the availability of learning resources (x3) positively impact students' mental health, while social support (x2) was found to have a negative effect. This study highlights the importance of motivation and academic support in promoting the mental well-being of students during the undergraduate thesis process.